Derrida and religion: other testaments - Sherwood, Yvonne; Hart, Kevin (Routledge, 2005)
Other Testaments / Yvonne Sherwood and Kevin Hart -- Epoché and faith: an interview with Jacques Derrida / John D. Caputo, Kevin Hart and Yvonne Sherwood -- Autochthony and welcome: discourses of exile in Lévinas and Derrida / Edith Wyschogrod -- Hosting / Gil Anidjar -- Mary, maternity, and Abrahamic hospitality in Derrida's reading of Massignon / Cleo McNelly Kearns -- Rosenzweig and Derrida at Yom Kippur / David Dault -- Christianity and Anti-Judaism / Walter Lowe -- Messianic epistemology / Robert Gibbs -- Midrash and the "magic language": reading without logocentrism / Daniel Boyarin -- Creatio ex libidine: reading ancient logos différantly / Virginia Burrus -- Other eyes: reading and not reading the Hebrew scriptures/Old Testament with a little help from Derrida and Cixous / Hugh S. Pyper -- To love the Tallith more than God / Timothy K. Beal and Tod Linafelt -- Derridapocalypse / Catherine Keller and Stephen Moore -- Otobiographies, or how a torn and disembodied ear hears a promise of death (a prearranged meeting between Yvonne Sherwood and John D. Caputo and the Book of Amos and Jacques Derrida) / Yvonne Sherwood and John D. Caputo -- The Word becomes text: a dialogue between Kevin Hart and George Aichele / Kevin Hart and George Aichele -- Sacrifice and secularization: Derrida, de Vries, and the future of mourning / Tyler Roberts -- Secrets and sacrifices of scission / Inge Birgitte Siegumfelt -- Deconstruction, God, and the possible / Richard Kearney -- The Revelation according to Jacques Derrida / John P. Manoussakis -- Aporia or excess? two strategies for thinking r/Revelation / Robyn Horner -- The Revelation of justice / Regina M. Schwartz -- Touching transcendence: sexual difference and sacrality in Derrida's Le Toucher / Ellen T. Armour -- Untouchable / Gregg Lambert -- Touching (in) the desert: who goes there? / Grace M. Jantzen -- El Tocado (Le Toucher): sexual irregularities in the translation of God (The Word) in Jesus / Marcella Maria Althaus-Reid